Quality of Life Is Not Deteriorated After Extrapleural Pneumonectomy vs. (Extended) Pleurectomy/Decortication in Patients With Malignant Pleural Mesothelioma - Lauk, Olivia; Patella, Miriam; Neuer, Thomas; Inci, Ilhan; Weder, Walter; Opitz, Isabelle (Frontiers in Surgery, 2021)
Background: Extrapleural pneumonectomy (EPP) for malignant pleural mesothelioma (MPM) is highly abandoned due to high morbidity and mortality rates and impaired quality of life (QoL). However, there are still rare indications for this intervention. The aim of this longitudinal prospective study was to monitor QoL and lung function in patients undergoing EPP and compare the outcomes with extended pleurectomy/decortication [(E)PD]. Methods: Between June 2013 and June 2017, 42 patients underwent induction chemotherapy followed by either EPP (n = 7) or (E)PD (n = 35). All patients filled out the EORTC QLC-C15-PAL, –LC13, and SF-36 self-rating questionnaires pre-operatively, 6 weeks and 4 months after the operation. Additionally, lung function was measured pre-operatively and 4 months post-operatively. Results: We observed no significant differences in all QoL categories (general global health, pain, and dyspnea) between both surgical procedures, over the whole observation period. Moreover, a general tendency toward restoration of the pre-operative QoL status was documented at 4 months after the both operations. Forced expiratory volume in 1 s (FEV1) showed a significant decrease after surgery in both the groups [EPP group p = 0.06 and (E)PD group p < 0.001]; also, the forced volume vital capacity (FVC) significantly decreased (EPP group p = 0.046 P/D group <0.001). Diffusion capacity did not show significant changes. Conclusion: According to these results, QoL is no longer severely impaired after EPP compared with EPD, and therefore should not be used as an argument against EPP in principle. However, indication has to be carefully evaluated for each patient.